Hyponatremia in elderly patients with fragility fractures of the proximal femur: a cross-sectional study - Aída Fernanda Batista Rocha; Marcus Villander Barros De Oliveira Sá; Ubirace Fernando Elihimas Junior (Brazilian Journal of Nephrology)
ABSTRACT Introduction: Proximal femur fractures affect the mortality and morbidity of elderly individuals. Recent studies have shown an association between fragility fractures and hyponatremia, a common fluid and electrolyte balance disorder. Objectives: This study aimed to investigate the occurrence of hyponatremia in patients with fragility fractures of the proximal femur. Methods: The authors looked into the data from the medical records of patients admitted to the emergency unit of the Real Hospital Português for fragility fractures of the proximal femur from 2014 to 2017. The study included patients with serum sodium levels recorded in their charts. Results: Fourteen of 69 (20.3%) patients with proximal femur fractures had hyponatremia. The main factors linked to hyponatremia were lung disease, and prescription of amiodarone and/or antidepressants. Conclusion: In elderly individuals, fragility fractures of the proximal femur may correlate with hyponatremia, particularly among patients on amiodarone or antidepressants.